2012
DOI: 10.1152/ajpgi.00458.2011
|View full text |Cite
|
Sign up to set email alerts
|

IL-1β stimulation of CCD-18co myofibroblasts enhances repair of epithelial monolayers through Wnt-5a

Abstract: Raymond M, Marchbank T, Moyer MP, Playford RJ, Sanderson IR, Kruidenier L. Il-1␤ stimulation of CCD-18co myofibroblasts enhances repair of epithelial monolayers through Wnt-5a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…In the future, we will examine if abnormal occlusion (causing mechanical changes in TMJ tissue) will induce β-catemn signalling activation in TMJ tissue. In addition to mechanical loading, growth factors involved in inflammation, such as tumour necrosis factor-α (TNF-α) and mterleukin 1β (IL-1β) could be potentially important upstream regulators for β-catenin signalling in TMJ tissues.It has been reported that TNF-α and IL-1β regulate β-catenin signalling in other tissues (Kitazawa et al ., 2011; Raymond et al ., 2012; Gong et al ., 2014). Regarding the mechamsm of β-catenin overexpression-induced defects in TMJ tissue, we propose that one of the major downstream mediators for β-catemn signalling in the TMJ tissue is Runx2.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, we will examine if abnormal occlusion (causing mechanical changes in TMJ tissue) will induce β-catemn signalling activation in TMJ tissue. In addition to mechanical loading, growth factors involved in inflammation, such as tumour necrosis factor-α (TNF-α) and mterleukin 1β (IL-1β) could be potentially important upstream regulators for β-catenin signalling in TMJ tissues.It has been reported that TNF-α and IL-1β regulate β-catenin signalling in other tissues (Kitazawa et al ., 2011; Raymond et al ., 2012; Gong et al ., 2014). Regarding the mechamsm of β-catenin overexpression-induced defects in TMJ tissue, we propose that one of the major downstream mediators for β-catemn signalling in the TMJ tissue is Runx2.…”
Section: Discussionmentioning
confidence: 99%
“…In primary mouse microglia cells, 300 ng/mL Wnt-5a increased proliferation [33], whereas treatment of cholangio-carcinoma cells with rWnt-5a decreased cell proliferation in vitro [34]. In the context of the initiation and coordination of intestinal epithelial repair, a human colon carcinoma cell line Caco2 and an epithelial cell line from normal colon NCM460 were treated with Wnt-5a (2.5-600 ng/mL), whereby rWnt-5a enhanced cell migration at 20-400 ng/mL but proliferation only at concentrations >100 ng/mL [35]. Yet, Wnt-5a has been reported to protect, in a dose-dependent manner, germinal centre B cells from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, IL-1β induced the overexpression of Wnt5a in CCD-18Co, an essential molecule of epithelium integrity and regeneration. Conditioned media depleted from Wnt5a failed to promote epithelial migration and differentiation, indicating that IL-1β indirectly induces epithelial migration through its direct action on myofibroblasts’ ability to express Wnt5a [70]. However, increased local and systemic IL-6 levels have been mainly associated with disease activity and severity.…”
Section: From Endothelial and Epithelial Injury To Myofibroblast Actimentioning
confidence: 99%